PENGARUH INVESTASI, TENAGA KERJA DAN KONSUMSI TERHADAP PERTUMBUHAN EKONOMI DI KOTA PADANG - AMINAH, AMINAH; Del Rosa, M.Si, Dra. Yenni; S.Pd, ME, Jolianis, (Pendidikan Ekonomi, 2014)
ABSTRACTIndicators used in this study is to determine the condition of the economy of a region. Purpose of this study was to determine the effect of investment, employment and consumption simultaneously and partially on economic growth in the Padang City. Collecting data related to economic growth, investment, employment and consumption obtained from the central statistical agency agencies Padang City. This study uses multiple non-linear regression, hypothesis testing to test the simultaneous effect of independent variable we used the F test , partial test using the t test. Results showed simultaneous and partial level of investment, employment and consumption have a significant effect on economic growth in the Padang City.Â